Reaction of diazepam and related benzodiazepines with chlorine. Kinetics, transformation products and in-silico toxicological assessment. (1st September 2017) - Carpinteiro, Inmaculada; Rodil, Rosario; Quintana, José Benito; Cela, Rafael
Abstract: In this work, the reaction of four benzodiazepines (diazepam, oxazepam, nordazepam and temazepam) during water chlorination was studied by means of liquid chromatography-quadrupole-time of flight-mass spectrometry (LC-QTOF-MS). For those compounds that showed a significant degradation, i.e. diazepam, oxazepam and nordazepam, parameters affecting to the reaction kinetics (pH, chlorine and bromide level) were studied in detail and transformation products were tentatively identified. The oxidation reactions followed pseudofirst-order kinetics with rate constants in the range of 1.8–42.5 M −1  s −1, 0.13–1.16 M −1  s −1 and 0.04–20.4 M −1  s −1 corresponding to half-life values in the range of 1.9–146 min, 1.8–87 h and 2.5–637 h for oxazepam, nordazepam and diazepam, respectively, depending of the levels of studied parameters. Chlorine and pH affected significantly the reaction kinetics, where an increase of the pH resulted into a decrease of the reaction rate, whereas higher chlorine dosages led to faster kinetics, as expected in this case. The transformation of the studied benzodiazepines occurs mainly at the 1, 4-diazepine 7-membered-ring, resulting in ring opening to form benzophenone derivatives or the formation of a 6-membered pyrimidine ring, leading to quinazoline derivatives. The formation of these by-products was also tested in real surface water samples observing kinetics of oxazepam degradation slower in river than in creek water, while the degradation of the two other benzodiazepines occurred only in the simpler sample (creek water). Finally, the acute and chronical toxicity and mutagenicity of precursors and transformation products were estimated using quantitative structure-activity relationship (QSAR) software tools: Ecological Structure Activity Relationships (ECOSAR) and Toxicity Estimation Software Tool (TEST), finding that some transformation products could be more toxic/mutagenic than the precursor drug, but additional test would be needed to confirm this fact. Graphical abstract: Highlights: From 4 BZPs 3 significantly react with chlorine: diazepam, oxazepam and nordazepam. Kinetics dominated by chlorine level & in the case of oxazepam and diazepam also pH. LC-QTOF-MS/MS permitted the identification of 9 transformation products. Transformation route generated mainly benzophenone and quinazoline derivatives. Some transformation products would be more toxic/mutagen than drug precursor.